2019
DOI: 10.16965/ijar.2019.115
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Study of Human Lungs

Abstract: Background and aims: Knowledge of anatomical variations in lung morphology is not only of academic interest but is essential during surgery and also while interpreting various radiological images. The present study was undertaken with the aim to observe the variations of lung morphology. Materials and Methods:The shape of the lungs, variations of fissures, lobes and hilar structures were studied in 42 right and 37 left isolated lungs.Results: Unusual shape was seen in 4 lungs. Among the right lungs, oblique fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Most frequently noted abnormalities consisted of variable numbers of lung lobes and branches of the pulmonary vasculature. [17][18][19][20][21][22][23][24][25][26][27] Fewer studies depicted anomalies in the pulmonary hilum, and even then, their focus remained on the numerical variations of the entering structures, rather than their topographical relationships. [24][25][26] Given that variability of pulmonary structures is not a rare finding in the patient population, the fact that none of the studies reported abnormal locations of pulmonary arteries and bronchi in the hilum signifies uniqueness of our case.…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation
“…Most frequently noted abnormalities consisted of variable numbers of lung lobes and branches of the pulmonary vasculature. [17][18][19][20][21][22][23][24][25][26][27] Fewer studies depicted anomalies in the pulmonary hilum, and even then, their focus remained on the numerical variations of the entering structures, rather than their topographical relationships. [24][25][26] Given that variability of pulmonary structures is not a rare finding in the patient population, the fact that none of the studies reported abnormal locations of pulmonary arteries and bronchi in the hilum signifies uniqueness of our case.…”
Section: Dovepressmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25][26][27] Fewer studies depicted anomalies in the pulmonary hilum, and even then, their focus remained on the numerical variations of the entering structures, rather than their topographical relationships. [24][25][26] Given that variability of pulmonary structures is not a rare finding in the patient population, the fact that none of the studies reported abnormal locations of pulmonary arteries and bronchi in the hilum signifies uniqueness of our case. Therefore, our report serves a clinically meaningful function of questioning the common belief that the spatial relationship between arteries and bronchi in the hilum is constant.…”
Section: Dovepressmentioning
confidence: 99%